Urinary Complications after Radical Hysterectomy in Cervical Cancer: A Retrospective Cohort Study - Muhammad Edo Antariksa Pradoto; Sutrisno Sutrisno; Dian Tjahyadi (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2025)
Objective: Radical hysterectomy and pelvic lymphadenectomy are standard treatments for cervical cancer. A common long-term complication is lower urinary tract dysfunction (LUTD), which can lead to urinary tract infections (UTIs) due to urinary stasis. Incontinence may also increase UTI risk by allowing bacteria to enter through the urethra. This study aims to determine the incidence of LUTD and UTI in cervical cancer patients after radical hysterectomy and to analyze their relationship.Methods: A retrospective cohort study was conducted on patients with stage IA2–IIA2 cervical cancer who underwent radical hysterectomy at Margono Soekarjo General Hospital. Urinary catheters were placed postoperatively, and bladder training was initiated on postoperative day three. Urine samples were collected on day fourteen or upon the return of bladder sensation to assess for urinary tract infection (UTI). The relationship between lower urinary tract dysfunction (LUTD) and UTI was analyzed using.Result: LUTD incidence was 13.8%. UTI incidence was significantly higher in patients with LUTD than in those without (7.7% vs. 1.5%, p < 0.001). The relative risk of UTI in patients with LUTD was 31.1 (95% CI: 6.396–739.029), likely due to the limited sample size.Conclusion: There is a significant association between LUTD and UTI in cervical cancer patients after radical hysterectomy. Early detection and monitoring of bladder function are essential in postoperative care.Keywords: Lower urinary tract dysfunction; radical hysterectomy; urinary tract infection.Komplikasi Urinaria Setelah Histerektomi Radikal pada Kanker Serviks: Studi Kohort RetrospektifAbstrak Tujuan: Histerektomi radikal dan limfadenektomi pelvik merupakan terapi standar untuk kanker serviks. Salah satu komplikasi jangka panjang yang umum adalah disfungsi saluran kemih bagian bawah (Lower Urinary Tract Dysfunction/LUTD), yang dapat menyebabkan infeksi saluran kemih (ISK) akibat stasis urin. Inkontinensia urin juga dapat meningkatkan risiko ISK melalui masuknya bakteri melalui uretra. Penelitian ini bertujuan untuk mengevaluasi insidensi LUTD dan ISK pada pasien kanker serviks pasca-histerektomi radikal tipe II serta hubungan antara keduanya.Metode: Sebuah studi kohort retrospektif dilakukan pada pasien kanker serviks stadium IA2–IIA2 yang menjalani histerektomi radikal di RSUD Margono Soekarjo. Setelah operasi kateter urin dipasang dan melatih kandung kemih dimulai pada hari ketiga pascaoperasi. Sampel urin dikumpulkan pada hari keempat belas atau saat sensasi kandung kemih kembali untuk menilai adanya infeksi saluran kemih (ISK). Hubungan antara disfungsi traktus urinarius bawah (LUTD) dan ISK dianalisis menggunakan uji Fisher’s exact.Hasil: Penelitian ini menunjukan insidensi LUTD adalah 13,8%. Insidensi ISK secara signifikan lebih tinggi pada pasien dengan LUTD dibandingkan yang tidak mengalami LUTD (7.7% vs. 1.5%, p < 0.001). Risiko relatif ISK pada pasien dengan LUTD adalah 31.1 (CI 95%: 6.396–739.029) karena jumlah subjek penelitian sedikit.Kesimpulan: Terdapat hubungan yang signifikan antara LUTD dan kejadian ISK pada pasien kanker serviks pasca-histerektomi radikal. Deteksi dini dan pemantauan fungsi kandung kemih sangat penting dalam perawatan pascaoperasi.Kata kunci: Disfungsi urin; histerektomi radikal; infeksi saluran kemih